On Green Pastures - Safat, Ilgar (Azerbaijan : Nariman Mammadov, 2006)
For two hundred years, Azerbaijan Mountains have been inhabited by “mоlоkans”, exiled from Russia in Catherine Second’s time. Old Believers live apart, namely in communities: their patriarchal way of life remains almost invariable during these two hundred years. “Mоlоkans” are devout and hardworking people retaining the tradition of “pre-Petrine” Russia, but coexist scanty in cultural inlay of Azerbaijan. The movie is about their amazing community.
Verzio Film Festival Submission